IMPACT OF LIVER STEATOSIS ON GLYCEMIC IMPROVEMENT AT SIX MONTHS AFTER BARIATRIC SURGERY - Moh, Mei Chung; Sze, Kenny Ching Pan; Hameed, Sharon Nadiyah Binte Shahul; Lim, Boon Khim; Pandian, Bhuvaneswari; Subramaniam, Tavintharan; Sum, Chee Fang; Lim, Su Chi (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVES Non-alcoholic fatty liver disease (NAFLD) is strongly associated with obesity and increases the risk of type 2 diabetes (T2D) development. This pilot prospective study aimed to determine whether the severity of liver steatosis/ fibrosis was associated with glycaemic improvement after bariatric surgery in adults with T2D. METHODOLOGY Patients with T2D scheduled for either Roux-en-Y gastric bypass or sleeve gastrectomy were recruited (n = 15; age: 46 ± 8 years, 46.7% males, body mass index (BMI): 40.8 ± 6.1 kg/m²). Transient elastography with controlled attenuation parameter (CAP) was performed before surgery to assess liver steatosis and fibrosis. The study outcomes included relative percentage change in glycated haemoglobin (HbA1c) at 6-month post-surgery from baseline (pre- op), and T2D remission defined as 6-month HbA1c<6.5% without glucose-lowering medications. HbA1c levels reduced from 7.4±1.4% to 6.3±1.0% at 6 months after surgery. The median relative percentage decrease in HbA1c was 13.4% (interquartile range: -25.8 to -6.3). The baseline CAP score (mean: 342 ± 50 dB/m; reflecting liver steatosis), but not the liver stiffness measurement score (reflecting liver fibrosis), was correlated with the relative percentage change in HbA1c (rho = 0.64, P=0.034). Linear regression analysis shows that higher CAP value was associated with reduced magnitude of HbA1c reduction (B = 0.21, 95% CI:0.06−0.36, P=0.017) after adjustment for baseline age, sex, BMI and HbA1c. Similarly, lower CAP score independently predicted T2D remission (relative risk=0.96, 95% CI:0.94−0.97, P<0.001). CONCLUSIONS Increased liver steatosis is associated with poorer glycaemic outcome after bariatric surgery. Therefore, interventions to reduce liver steatosis prior surgery may improve post- surgical glycaemic control in people with T2D.